2022
DOI: 10.1002/cdt3.47
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory questionnaire‐based analysis of awareness of COPD in a large multicenter rural population‐based study in India

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a more prevalent chronic lung disease with a significant health burden, and the majority of these cases receive inadequate treatment. Methods: Prospective, observational, interview (questionnaire) based complete workup COPD study, screened 12,000 cases with chronic respiratory symptoms with cough, sputum production, and shortness of breath. A total of 6000 COPD cases were enrolled after the spirometry test. COPD cases were assessed as disease knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…More than half of the respondents were unaware that COPD is a common disease and nearly 60% of the participants did not know that COPD increases mortality, despite COPD being ranked as the third leading cause for mortality globally [ 11 ]. Although lower COPD acceptance rates were also reported in Australia [ 43 ] and India [ 44 ], this poor level of beliefs and perception is particularly higher in Saudi Arabia possibly due to social pressure since most Saudi youths socialize mostly in indoors and areas with high exposure to passive smoking [ 8 ]. Therefore, there is a paramount necessity to provide valid information to the Saudi public regarding the nature, prevalence, risk factors, and the long-term consequences of COPD including the alarming reduction in disability-adjusted life years (DALYs) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the respondents were unaware that COPD is a common disease and nearly 60% of the participants did not know that COPD increases mortality, despite COPD being ranked as the third leading cause for mortality globally [ 11 ]. Although lower COPD acceptance rates were also reported in Australia [ 43 ] and India [ 44 ], this poor level of beliefs and perception is particularly higher in Saudi Arabia possibly due to social pressure since most Saudi youths socialize mostly in indoors and areas with high exposure to passive smoking [ 8 ]. Therefore, there is a paramount necessity to provide valid information to the Saudi public regarding the nature, prevalence, risk factors, and the long-term consequences of COPD including the alarming reduction in disability-adjusted life years (DALYs) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various Chronic respiratory diseases are common in India including COPD, asthma, bronchiectasis, interstitial lung diseases and post-tuberculosis obstructive airways diseases. Authors have observed 43% cases were difficult to accept COPD diagnosis, 91% cases did not receive rational inhalation treatment and 42% cases were treated with oral medicines over rational inhalation treatment in their study in rural settings in India [2].…”
Section: Introductionmentioning
confidence: 88%
“…Globally, Inhalation treatment method is the preferred route of administration of drug for treatment of COPD and considered as 'lung targeted therapy' and evidence-based medicine has observed significant improvement in symptom control and lesser systemic side effects due to smaller volume of drug used as compared to oral or intravenous route of administration [13]. Authors have mentioned high cost of long-acting or rational inhalation treatments and improper drug selection by family physicians was the reason for least preference to inhalation medicines over oral medicines [2]. Similarly, various studies [14][15] have mentioned COPD management remains suboptimal due to lack of knowledge or unawareness regarding current guidelines by treating physicians, and poor adherence by patients to prescribed medicines regarding usefulness of rational inhalation treatment.…”
Section: Factors Affecting Less Preference For Inhaled Medicines or R...mentioning
confidence: 99%
See 1 more Smart Citation